2014
DOI: 10.5721/eujrs20144721
|View full text |Cite
|
Sign up to set email alerts
|

A regional level preliminary landslide susceptibility study of the upper Indus river basin

Abstract: The major goal of this research was to explore low cost means by which large tracts of mountainous terrain (~75000 km 2 ) can be screened for landslide-related hazards. For upper Indus watershed study, landslide susceptibility index maps were generated by coupling two main indicators groups: 1) environmental risk factors, which mainly contain slope angle, slope aspect, elevation, lithology maps; and 2) the causative factors, which include seismicity and rainfall. GIS based expert driven weighted overlay and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…For this reason, the slope has been considered as an important factor in this study as well. [9] expresses that, according to the documented land and Moreover, the finding demonstrated that the weaker rocks which are loosely held are more prone to falling. It is widely recognized that geology of an area, greatly influences the occurrence of landslides and rock falls in that particular area.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…For this reason, the slope has been considered as an important factor in this study as well. [9] expresses that, according to the documented land and Moreover, the finding demonstrated that the weaker rocks which are loosely held are more prone to falling. It is widely recognized that geology of an area, greatly influences the occurrence of landslides and rock falls in that particular area.…”
Section: Discussionmentioning
confidence: 91%
“…The aspect map (Figure 2 to certain elevations [10]. [9] investigated that 64% of reported landslides were recorded at elevation of 2000 -4000 m and 24% were observed at elevation of 1000 -2000 m. Buffers were created around the drainage network and classified into 0 -500 m, 500 -1500 m, 1500 -2500 m, 2500 -5000 m and <5100 m (Figure 2(d)). Landslides increase if the distance to streams or rivers is decreased, due to slope instability which leads to erosion.…”
Section: Data Acquisition and Preparation Of Causative Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all parameters for LS zonation, elevation, slope and aspect have been recognized as the most important conditioning factors [6][7][8][9]. The elevation dataset is useful to classify the local relief and locate points of maximum and minimum heights within terrains.…”
Section: Introductionmentioning
confidence: 99%
“…For an earthquake event, landslides occur preferentially on the hillslope of specific orientation with respect to the earthquake's epicenter or fault (Tibaldi et al, 1995). Auer and Shakoor, 1989;Jakob, 2000;Liu and Shih, 2013;Ahmed et al, 2014;Smith and Wegmann, 2018) due to orographic rainfall. For a rainfall event, landslides are prone to occur on the windward hillslopes (e.g.…”
Section: Introductionmentioning
confidence: 99%